Effect of planting density and growing media on growth and fruit production of okra (abelmuschus esculentus (L.)moench) - Noorizzatie, Abdul Rahim (Universiti Malaysia Sarawak (UNIMAS), 2015)
Abelmuschus esculentus (L.) Moench,is the vegetable that popular in Malaysia which originated from India. These plants are easy to grow and give fruit production in short time. The experiment was designed as 2 x 3 factorial design experiment. In this experiment, okra are in complete block variety with plant density which is 25cm x 50cm (D1) and 50cm x 50cm (D2). The growth of okra were compared in different media which is 1:1 topsoil:sand (M1); 1:1 topsoil:coco peat (M2); and hundred percent coco peat (M3). Hence the objectives of this study were to determine the best planting density and growing media on growth and fruit production okra. The result showed that the planting density was not significantly affecting growth and fruit production, while in the growing media, there were significantly affecting in number of leaf, number of branch, and diameter at specific week. There was significantly difference affecting the number of leaf, number of branch and growth of fruit in the relations between planting density with growing media. Seedling in D1 give the highest reading in all the growth performance of plants in their height, diameter, number of branch,number of leaf, total leaf area and shoots as biomass. Meanwhile in reading of fruits growth, D2 give the highest reading. Moreover, in growing media, M1 give the best reading of growth performance in height, diameter, number of leaf, total leaf area and biomass. In fruit performance growth, M3 gave the highest result. As the conclusion, D1 and M1 is the best planting and growing media for the growth of okra. While, D1 and M3 is the best planting density and growing media for fruit production.